CONCEPTUAL PRINCIPLES OF HOUSING DEVELOPMENT IN THE CONTEXT OF POST-WAR RECONSTRUCTION - Polyanska, Alla Stepanivna; Mykytiuk, Natalia; Mykytiuk, Oleg (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The connection between modern concepts that prevail in the field of construction in the global dimension and the situation that determines the prerequisites for their implementation in the conditions of Ukraine is considered. Based on the analysis of the publications of scientists who study the issue of post-war reconstruction and the tendencies in field of construction, the prospects, and possibilities of implementing modern concepts of the development of housing construction in Ukraine have been determined. The factors that determine the demand and supply for housing in the housing construction sector are characterized, as well as the peculiarities of their consideration in the process of creating demand for housing in the conditions of post-war recovery. The main approaches to the development of housing construction in the conditions of post-war reconstruction are characterized, in particular: the regional approach, which gives regions the opportunity to independently make decisions about reconstruction technologies based on taking into account the opinions of community members, the concept of sustainable construction, which prioritizes the possibilities of solving environmental problems in the construction process, and the concept of smart construction that uses modern digital technologies for sustainable, safe and efficient construction and operation of buildings. Significant factors that are not sufficiently studied and that create a significant impact on the development of housing construction, considering modern concepts. An analysis of the regulatory framework, which currently regulates the issue of post-war reconstruction, including its financial aspects, has been carried out. A survey of residents of Ivano-Frankivsk was conducted, based on the results of which strategies for the economical use of energy resources were selected to determine the cognitive map of the behaviour of consumers of construction products. It’s summarized that the readiness of the population and their knowledge and experience in the field of economical consumption of energy resources are of decisive importance in the choice of strategies for the economical use of energy resources. The obtained results can find further scaling and use by local self-government bodies, construction organizations, developers, scientists for the formation of programs and plans for post-war reconstruction and determination of directions and ways of implementing sustainable and smart construction.